2022
DOI: 10.1002/vms3.760
|View full text |Cite
|
Sign up to set email alerts
|

Betaretrovirus infections in dromedary camels in Saudi Arabia

Abstract: Background: Retroviral infections have been reported in many species of animals, especially cattle, sheep and goats. However, there are no available reports about retrovirus infection in dromedary camels. Several dromedary camels showed visible tumorlike lesions on and around the nostrils as well as around the eyes.Objectives: Following are the objectives: to identify the causative agents of these identified tumours in dromedary camels and to perform molecular characterization of the detected strains of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Since there is no vaccine available, an infection with JSRV in a flock is associated with high economic losses [ 78 ]. Recent studies also found retroviral sequences with similarity to JSRV and enzootic nasal tumor virus (ENTV; see Section 5.1.4 ) in dromedary camels in Saudi Arabia, which live in close proximity to sheep and goats, suggesting interspecies transmission [ 79 ].…”
Section: Which Animal Retroviruses From the Family Orthoret...mentioning
confidence: 99%
“…Since there is no vaccine available, an infection with JSRV in a flock is associated with high economic losses [ 78 ]. Recent studies also found retroviral sequences with similarity to JSRV and enzootic nasal tumor virus (ENTV; see Section 5.1.4 ) in dromedary camels in Saudi Arabia, which live in close proximity to sheep and goats, suggesting interspecies transmission [ 79 ].…”
Section: Which Animal Retroviruses From the Family Orthoret...mentioning
confidence: 99%